AKTIFITAS SOCIAL BENEFIT PERUSAHAAN DITINJAU DARI AKUNTANSI LINGKUNGAN DAN FIKIH LINGKUNGAN - Fatmawatie, Naning (EQUILIBRIUM, 2018)
The role of the company in addition to causing the social cost, in fact can also generate social benefits. Social benefit or benefits is the positive contribution to the public the company's existence. Social activities benefit the company to respond to the Law No. 32 of 2009 on the Protection and Environmental Management. Environmental accounting or accounting or accounting Economic Social Responsibility is an accounting concept that measures how far the company adverse impact and benefit to the community. Islamic jurisprudence is an overview of the environment in regulating the management and conservation of natural resources and the environment. Activity Relationships of social benefits with environmental accounting and environmental fiqh is that the economic development of sharia in Indonesia raise awareness of entrepreneurs to business practices that have an ethical responsibility in Islamic.Social activities benefit in terms of environmental accounting is that the disclosure of the results of environmental conservation activities in the form of accounting data. The information disclosed is quantitatively measured results of environmental conservation activities. Included is information on the economic resources of an enterprise, the claims to those resources (liabilities of a company to hand sources on other entities or owners of capital), and the effects of transactions, events and conditions that alter the economic resources and claims against the source. While the benefits of social activity in terms of environmental jurisprudence is that a review of Islam in governing the management and conservation of natural resources and the environment, he hoped could provide a fundamental change for the conservation of the environment.